Focusing on the human factor in environmental disasters. (29th January 2013) - Showstack, Randy
Abstract : "When I wake up in the morning, I'm wondering, Is this going to be the day for the 'aha, ' when leaders around the country will come to grips with the problems that are there in front of them and be responsive to the information they already have?" Gerald Galloway, an expert in water resource policy and civil engineering, said during a 16 January discussion about human factors in disasters. The discussion was part of the 13th National Conference on Science, Policy and the Environment, held in Washington, D. C.